Poverty Alleviation Strategy - Pairan, Pairan (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The objective of this research is to analyze the strategy of poverty alleviation in the field of economics, socials, and environments made by Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Perkotaan (cities self-supporting empowerment national programs). This research is a case study with the design of single case which has more than one unit analysis. By applying this method, it is hoped that the findings are able to describe how the strategies of poverty alleviation use the empowerment approach. The findings show that the strategy of poverty alleviation has been done by digging the society volunteer competencies who have to be the society cadres of poverty alleviation. These cadres and the facilitators who are the officials of PNPM have facilitated to found the local organization with the name of Lembaga Keswadayaan Masyarakat/LKM (self-supporting society institutions). This institution is an embryo of social capital which has a bride functions for making a synergies relationship from the poor to the sources that are able to use for poverty alleviation in the society and others. The process of poverty alleviation facilitation is by using trust, cooperative, and networking through the cycles of poverty alleviation. These cycles are; reflecting poverty, mapping self-supporting, founding the local organization, arranging the programs of poverty alleviation, forming KSM, and driving the activities on the priorities of economics, socials, and environment.